Modelling and Simulation of a Hip Abduction-Adduction Assistive Exoskeleton to Improve Elderly Stability - Burton, Thomas (Université d'Ottawa / University of Ottawa, 2023)
Walking Assist Exoskeletons are wearable devices that can allow individuals with mobility impairments to maintain their autonomy. The growing elderly population has benefited from these devices by receiving assistance at joints where their muscle function has declined. Typically, the primary objective of these exoskeletons has been to reduce the metabolic cost of walking, allowing users to walk for extended periods of time while reducing fatigue. However, this strategy does not directly address the growing concern that seniors are at an increased risk of falling and sustaining severe injuries due to falls. Gait and balance disorders are among the most common causes of falls in the elderly. As the Canadian population ages, it is increasingly important to investigate the musculoskeletal changes contributing to frontal-plane instability, as mediolateral and posterolateral falls are correlated with higher incidences of severe injuries. Specifically, the hip abductor and hip adductor muscles are essential in maintaining balance in the frontal plane, yet little research has been conducted on the effect of hip abduction-adduction exoskeleton assistance on the stability of elderly individuals. This thesis investigates the effect of introducing an assistive torque with a specific magnitude, timing, and location (i.e. applied to one or both legs) on the margin of stability of elderly individuals using the OpenSim biomechanics software. Simulations of four elderly subjects were conducted while the subjects stood in a quiet standing position with both feet on the ground. A lateral perturbation force of magnitude 5%, 10% or 15% of bodyweight was applied to the pelvis of each subject. The simulations were designed to provide elderly subjects with contralateral (i.e. the limb on the opposite side of the body as the perturbation), ipsilateral (i.e. the limb on the same side as the perturbation), or bilateral hip abduction-adduction assistive torque from a hip exoskeleton device after a perturbation force was applied to the pelvis. The simulated actuators mounted at the hip joints were massless, applied torque in the frontal plane, and could generate torque instantaneously based on user-defined inputs. The change in margin of stability was used to measure the effectiveness of each assistive strategy and for comparison across all subjects. The results of this study suggest that, as the perturbation magnitude increases, the hip abduction-adduction assistive exoskeleton should prioritize assistance applied to the contralateral limb. Regardless of the perturbation magnitude, each assistive strategy that was simulated (i.e. contralateral, ipsilateral and bilateral assistance) was able to improve the margin of stability. The greatest mean improvement on the margin of stability compared to the unassisted condition occurred when using the contralateral assistance strategy. For the 5%, 10% and 15% bodyweight perturbations, a contralateral assistance of 0.75 N·m/kg (torque normalized by the subject's mass) resulted in an improvement in the margin of stability of 13.1 ± 0.987 mm, 13.0 ± 0.946 mm and 13.1 ± 0.816 mm, respectively. The simulations also suggested that similar improvements on the margin of stability were experienced at smaller assistive torque magnitudes when the actuators provided torque to the body quicker following a perturbation. The results of this study can be used by exoskeleton designers to guide their decisions when developing abduction-adduction assistive exoskeletons that target mediolateral stability assistance in the elderly population.
Keywords: Balance; Elderly; Exoskeleton; Gait; Hip; Stability